(untitled) (Rudarsko-geološko-naftni zbornik, 2025)
Quenching is a general term for the rapid cooling of an austenitized hardenable steel or a solution treated aluminum alloy in liquid mediums with a boiling point lower than austenitization or annealing temperature. In this paper, an approach in development of a novel numerical method for computation of quenching of metal materials by immersion in liquids subjected to the Leidenfrost phenomenon has been described. Upon the known initial temperatures of the quenchant and the specimen, the numerical method by application of two-fluid VOF model solves the Stefan problem and the temperature distribution within the specimen in the first stage of quenching, in which the surface of the specimen is covered with the vapour film. The validation of the solution by comparison of the estimated temperature distribution with the experimental results from literature has been carried out, and the instantaneous distribution of the heat flow rate has been analyzed. The obtained results show the suitability of the suggested method for the numerical analysis of the initial phase of metal material immersion quenching.